Skin angiography assisted mastectomy in secondary breast angiosarcoma: Complete clinical response after neoadjuvant immunotherapy. Issue 9 (25th June 2021) - Ju, Tammy; Foster, Deshka; Titan, Ashley; Najjar, Saleh; Bean, Gregory R.; Ganjoo, Kristen; Wapnir, Irene
Abstract: Radiation‐induced breast angiosarcoma, or secondary angiosarcoma (SAS), is a rare entity with a high risk of metastatic recurrence. Herein, we describe the use of intraoperative fluorescence‐based skin angiography to guide surgical resection following a novel immunotherapy‐based regimen for SAS resulting in a complete pathological response.